2021
DOI: 10.24179/kbbbbc.2021-82151
|View full text |Cite
|
Sign up to set email alerts
|

Neurotological Manifestations of Patients with COVID-19

Abstract: Coronavirus disease-2019 (COVID-19) is the infectious disease caused by novel coronavirus [severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2)], which has spread all over the globe as a pandemic. At the point of starting vaccination programs, the number of confirmed cases of COVID-19 and deaths related to the disease has exceeded 75 million and 1.6 million since the start of the pandemic,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Several neurological and neuro-otological manifestations have been reported in association with coronavirus disease 2019 (Covid-19). [1][2][3] In particular, the number of cases or case series of sudden sensorineural hearing loss associated with Covid-19 has been widely reported in the literature. 4 While some studies have found an increase in the incidence of hearing loss during the pandemic compared to the pre-pandemic period, 5 controlled studies investigating the effect of Covid-19 on the hearing system have shown inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…Several neurological and neuro-otological manifestations have been reported in association with coronavirus disease 2019 (Covid-19). [1][2][3] In particular, the number of cases or case series of sudden sensorineural hearing loss associated with Covid-19 has been widely reported in the literature. 4 While some studies have found an increase in the incidence of hearing loss during the pandemic compared to the pre-pandemic period, 5 controlled studies investigating the effect of Covid-19 on the hearing system have shown inconsistent results.…”
Section: Introductionmentioning
confidence: 99%